THE IMPACT OF INFORMATION TECHNOLOGY GOVERNANCE ON THE VALUE RELEVANCE OF ACCOUNTING INFORMATION - Ali Marza Abdel Hamza Al-Issawi; Mohammed Hasan Kareem Al-Thabhawee; Tammar Saleh Jawad Hayder (Scholars Digest Publishing, 2024)
The research aims to demonstrate the importance of information technology governance. It also reflects its impact on the relevance of the value of accounting information. The research problem was formulated by asking the main question: Is there a statistically significant effect between information technology governance and the relevance of the value of accounting information? Relying on a questionnaire distributed to a sample of the community of accountants and auditors in banks listed on the Iraq Stock Exchange, where (165) questionnaires were distributed, the answers were retrieved at (123), and the results were analyzed using the SPSS software. The researcher used a simple linear regression model and simple Pearson correlation. After testing the research hypotheses, a set of conclusions were reached, the most important of which is the presence of a statistically significant effect of the dimensions of information technology governance on the importance of the value of accounting information. The most important recommendations emphasized by the research are that economic units should enhance relevant information technology governance practices to enhance the overall effectiveness of technology and information management.
Keywords: Information technology governance; Accounting information; Value relevance of accounting information.